1973
DOI: 10.1128/iai.8.6.876-881.1973
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and Immunogenic Efficacy of a Live Attenuated Plague Vaccine in Vervet Monkeys

Abstract: A live attenuated Yersinia pestis (Pasteurella pestis) vaccine strain designated EV51f, which had been passaged through guinea pigs previously treated with ferrous sulfate, was shown to be pathogenic for African green vervet monkeys (Cercopithecus aethiops pygerythrus), but not for guinea pigs. The bacilli multiplied in the monkeys, as shown by positive blood cultures, caused an elevation of white cell counts and rectal temperatures, and resulted in death of 26% (13/50) of animals. Postmortem findings of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Several species of non-human primates including hamadryas baboons [30,31], vervet monkeys, rhesus monkeys and African green monkeys have been used for evaluation of EV vaccines. It has been known that EV strain was shown to be virulent in African green monkeys and vervet monkeys, but not in rhesus monkeys and guinea pigs [32,33]. Welkos et al [34] reported that a pigmentation-deficient (Pgm)) strain of Y. pestis strain C092 was virulent in African green monkeys and outbred Swiss Webster mice by the aerosol route.…”
Section: Cardiac Blood Brainsmentioning
confidence: 99%
“…Several species of non-human primates including hamadryas baboons [30,31], vervet monkeys, rhesus monkeys and African green monkeys have been used for evaluation of EV vaccines. It has been known that EV strain was shown to be virulent in African green monkeys and vervet monkeys, but not in rhesus monkeys and guinea pigs [32,33]. Welkos et al [34] reported that a pigmentation-deficient (Pgm)) strain of Y. pestis strain C092 was virulent in African green monkeys and outbred Swiss Webster mice by the aerosol route.…”
Section: Cardiac Blood Brainsmentioning
confidence: 99%
“…The live EV76 vaccine is a spontaneous pgm mutant that has been used in humans for over 80 years in regions and countries of the former Soviet Union (FSU) without any deaths reported [1][2][3]. The EV76 vaccine conferred better protection against bubonic and pneumonic plague than killed vaccines in different animals, but it sometimes caused local and systemic reactions including fever, malaise, lymphadenopathy, erythema and large induration at the injection site [4][5][6][7], as well as disease in primates [6]. In addition, the live Pgm − strain (Y. pestis KIM5) retained virulence by intranasal (i.n.)…”
Section: Introductionmentioning
confidence: 99%
“…The serological response of Praomys to the vaccine strain is poor compared with Cercopithecus aethiops (15). Only high doses stimulated plague HA antibodies, the highest titer recorded being 1:1,024 (geometric mean titer = 239).…”
Section: Discussionmentioning
confidence: 91%
“…Live attenuated plague vaccines that pass safety tests in guinea pigs and white mice have been found to be virulent in nonhuman primates (15,22). The expense and difficulty in obtaining these animals prompted an investigation of the reaction of Praomys (Mastomys) na-talensis, a highly susceptible rodent species, to live attenuated Y. pestis vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation